STRES OKSIDATIF PEMICU UTAMA KEMATIAN SEL PURKINJE OTAK KECIL (CEREBELLUM ) - Saichudin, Saichudin (Jurnal Sport Science, 2014)
Abstract :The human body under normal conditions have a balance formation of radicals with the antioxidant system of the body. The activity of radicals and other oxygen can be controlled antioxidant sytem in order not to disrupt the continuity of biological processes. Even some biological processes take place using a compound of radicals as mediator. When the body balance is disturbed, the number of radicals increases or antioxidant system decreases. As a result, there will be pathological reactions between radicals with biological molecules in the body. Therefore, the structure and function of biological molecules the body can be changed. This event is called oxidative stress. Oxidative stress, one of which can cause brain cell death (cerebellum). Test results vary between BB and BBA (ns), TBBA and Control (ns), BB and TBBA (s), B and control (s), BBA and TBBA (s), BBA and Control (s). Conclusion: motor stimulation varied greatly affect the morphology of the cerebellum and morphological improvement will improve the quality of physiological Cerebellum Cerebellum.Key words :oxidative stress, cell death in the cerebellum.Abstrak :Tubuh pada kondisi normal mempunyai keseimbangan antara pembentukan senyawa radikal dengan sistem antioksidan tubuh. Aktivitas senyawa radikal dan oksi-gen lain dapat dikendalikan oleh sistem antioksidan sehingga tidak sampai mengganggu kelangsungan proses biologis, bahkan sebagian proses biologis berlangsung dengan menggunakan senyawa radikal untuk mediator. Bila keseimbangan tubuh terganggu maka jumlah senyawa radikal sangat meningkat atau sistem antioksidan tubuh sangat menu-run. Dengan demikian reaksi patologis antara senyawa radikal dengan molekul biologis tubuh akan terjadi sehingga struktur dan fungsi molekul biologis tubuh dapat berubah. Peristiwa ini disebut stres oksidatif. Stres oksidatif salah satunya dapat menyebabkan kematian sel otak kecil (cerebellum). Hasil uji beda antara BB dan BBA (ns), TBBA dan Kontrol(ns), BB dan TBBA(s), BB dan Kontrol (s), BBA dan TBBA(s), BBA dan Control(s). Kesimpulan: variatif rangsangan motorik sangat mempengaruhi morfologi Cerebellum dan peningkatan morfologi Cerebellum akan meningkatkan kualitas fisiologi Cerebellum.Kata kunci :stres oksidatif, kematian sel cerebellum.